2020
DOI: 10.1155/2020/8825456
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical and Experimental Study on Esterification of Citric Acid with the Primary Alcohols and the Hydroxyl Groups of Cellulose Chain (n = 1-2) in Parched Condition

Abstract: Esterification of citric acid (CA) with the primary alcohols and the hydroxyl groups of cellulose chain (n = 1-2) in parched condition were investigated by using density functional theory (DFT) method and a two-layer ONIOM approach. Geometry and energy of reactants, products, and transition state (TS) structures were optimized at B3LYP/6-311g (d, p) level and ONIOM (B3LYP/6-311g (d, p):PM3MM) level. The computational results show that the esterification occurs in the two main steps: the first step is the dehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Demitri et al have, for the first time, reported crosslinking of cellulose derivative with citric acid (CA) [3]. By dissociation of a water molecule from two adjacent carboxyls at increased temperature (for example, 80 °C overnight [3] or 8 h [4], 100 ° C for 5 min [5] or 50 °C for 15 h which is temperature allowing for living bacteria incorporation [6] and so on), the polyvalent carboxylic acid can be transformed into anhydrite form which is capable to form ester bond with a hydroxyl group [7,8]. To achieve this type of crosslinking, polysaccharides should be water-soluble, and they should contain a sufficient amount of hydroxyl moieties.…”
Section: Introductionmentioning
confidence: 99%
“…Demitri et al have, for the first time, reported crosslinking of cellulose derivative with citric acid (CA) [3]. By dissociation of a water molecule from two adjacent carboxyls at increased temperature (for example, 80 °C overnight [3] or 8 h [4], 100 ° C for 5 min [5] or 50 °C for 15 h which is temperature allowing for living bacteria incorporation [6] and so on), the polyvalent carboxylic acid can be transformed into anhydrite form which is capable to form ester bond with a hydroxyl group [7,8]. To achieve this type of crosslinking, polysaccharides should be water-soluble, and they should contain a sufficient amount of hydroxyl moieties.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the CA triacid will form anhydrides at ∼120 °C, and then react with primary alcohols without the use of catalysts or strong acids. 44,45 In our experiments, the cellulose and cellulose-CA microbeads are produced at a nozzle temperature between 120 and 175 °C. With the microsphereequipped AFM probe, we explored the effect of spray dryinginduced crosslinking of cCNC particles with guest CA molecules and their impact on the microsphere elastic modulus.…”
Section: Adjusting the Young's Modulus In Ccnc Microbeads By Simultan...mentioning
confidence: 99%
“…It seems that citric acid reduces the curing temperature of a crude glycerol based liquefied PKS product. Citric acid was dehydrated to form cyclic anhydrides with water as byproduct, before further crosslinking with the free hydroxy groups within glycerol-based liquefied PKS products through esterification, which requires a low reaction energy (Nguyen and Pham 2020). Consequently, the total energy consumption for curing crude glycerol-based liquefied PKS was reduced from 159 J/g to 148 J/g on adding 15% citric acid.…”
Section: Thermal Behavior Of Glycerol-based Liquefied Pks and Its Ble...mentioning
confidence: 99%
“…In the presence of heat, the esterification process is likely initiated through the dehydrative transformation of the citric acid, resulting in the formation of an intermediate anhydride ring, giving water as a byproduct. Subsequently, this anhydride ring undergoes esterification with a hydroxy group, leading to the opening of the ring and the production of the final ester product (Nguyen and Pham 2020). The anhydride ring of citric acid can be formed at its melting point around 153 °C (Noordover et al 2007).…”
Section: Introductionmentioning
confidence: 99%